2011
DOI: 10.1177/0194599811400977
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nasal Obstruction on Obstructive Sleep Apnea

Abstract: Postoperative nasal packing aggravated measures of OSA in patients with mild OSA but not in patients with moderate/severe OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 23 publications
(59 reference statements)
3
39
0
3
Order By: Relevance
“…8 This may be due to increased likelihood of mouth breathing, which is associated with a higher upper airway resistance as compared with nasal breathing (5.65 cm H 2 O/L/s with nasal breathing vs 14.9 cm H 2 O/L/s, P = .005). 8 Similarly, if the nasal bones were broken, as occurs when osteotomy is performed in rhinoplasty, postoperative use of a CPAP mask that involves the nose (eg, nasal mask, nasal pillows, full-face mask) may be contraindicated, as it may affect the healing process. Therefore, it would be advisable to coordinate the care of such patients with their sleep specialists to discuss alternative mask options, such as switching to different mask options (eg, an oral interface or total face mask options), or alternative treatment options (eg, positional therapy, an oral appliance device, hypoglossal nerve stimulator).…”
Section: Supporting Textmentioning
confidence: 99%
“…8 This may be due to increased likelihood of mouth breathing, which is associated with a higher upper airway resistance as compared with nasal breathing (5.65 cm H 2 O/L/s with nasal breathing vs 14.9 cm H 2 O/L/s, P = .005). 8 Similarly, if the nasal bones were broken, as occurs when osteotomy is performed in rhinoplasty, postoperative use of a CPAP mask that involves the nose (eg, nasal mask, nasal pillows, full-face mask) may be contraindicated, as it may affect the healing process. Therefore, it would be advisable to coordinate the care of such patients with their sleep specialists to discuss alternative mask options, such as switching to different mask options (eg, an oral interface or total face mask options), or alternative treatment options (eg, positional therapy, an oral appliance device, hypoglossal nerve stimulator).…”
Section: Supporting Textmentioning
confidence: 99%
“…Therefore, it is not surprising that our results suggest that children with palatal involvement (CP and CL+P) present more frequently with symptoms of OSA. Lastly, nasal airway obstruction, which may be present in patients with CL+P [11], may predispose to airway collapse and OSA [12,13].…”
Section: Primary Anatomic Osamentioning
confidence: 99%
“…Multiple studies have shown an association of nasal airway obstruction with OSA. Specifically, OSA has been noted to be twice as prevalent in patients with nasal airway obstruction [12]. Increased nasal airway resistance creates proportionately increased negative pressure in the pharynx, predisposing to collapsibility of the pharyngeal cavity and likely contributing to the pathogenesis of OSA [13].…”
Section: Patient Evaluation and Managementmentioning
confidence: 99%
“…No presente estudo, foi encontrada relação estatisticamente significante entre os graus de apneia com a presença de obstrução nasal, com a intensidade do ronco e a Escala de sonolência de Epworth, quando comparados ao grupo com Ronco Primário, resultado este discordante com os da literatura (16) . Conforme referido anteriormente, embora o sítio primário de colapso nos pacientes com SAOS seja a parte oral da faringe e a parte laríngea da faringe, estudos demonstram uma significativa associação entre a obstrução nasal e a SAOS (8)(9)(10) , o que foi confirmado no presente estudo. Além do simples efeito da obstrução nasal no padrão de respiração durante o sono, o nariz é o maior condutor de ar para tratamento da SAOS com o aparelho de Pressão Positiva Contínua nas Vias Aéreas (CPAP).…”
Section: Grupo I -Com Saos (142 Pacientes -73%)unclassified
“…Doenças inflamatórias da mucosa do nariz, ou alterações estruturais, como desvio de septo nasal, hipertrofia das conchas, lesões traumáticas, lesões neoplásicas, pólipos, colapso da válvula nasal, hipertrofia de adenoides e corpos estranhos, podem ser as principais causas de obstrução nasal (6) . Embora o sítio primário de colapso nos pacientes com SAOS seja a parte oral da faringe e a parte laríngea da faringe, estudos demonstram uma significativa associação entre a obstrução nasal e a SAOS (8)(9)(10) . Este estudo tem como objetivo verificar a associação de obstrução nasal em pacientes com queixas de distúrbios respiratórios relacionados ao sono, encaminhados a um Ambulatório de Ronco e Apneia de Sono.…”
Section: Introductionunclassified